Aceite esencial de palo de rosa (Aniba Rosaeodora): capacidad antioxidante y antibacteriana - Davila Briceño, Stalin Junior (2025)
The objective of this research was to evaluate the antioxidant capacity and antibacterial activity of the essential oil of Aniba Rosaeodora (rosewood), a species native to the Peruvian Amazon. The study was developed under an experimental approach, using bark and wood as raw material for the extraction of the oil by steam extraction. Antioxidant capacity was determined by DPPH, ABTS and Folin-Ciocalteu methods, while antibacterial activity was evaluated by the agar diffusion method (Kirby-Bauer) against six reference bacterial strains, both Gram-positive and Gram-negative. The results showed a high antioxidant capacity, with average values of 721.62 ± 22.02 µmol/g DM (DPPH), 936.08 ± 16.72 µmol/g DM (ABTS) and 7539.85 ± 219.75 mg AG/g DM (total phenols), which evidences the high content of bioactive compounds such as flavonoids, tannins and triterpenes. In terms of antibacterial activity, the oil showed greater efficacy against Gram-positive bacteria, especially Staphylococcus aureus and Salmonella Typhimurium, with inhibition zones greater than 16 mm at high concentrations, while Pseudomonas aeruginosa was resistant. It is concluded that the essential oil of Aniba Rosaeodora has an important potential as a natural preservative due to its antioxidant and antibacterial effect, being a viable alternative for the food and pharmaceutical industry. In addition, its sustainable use could contribute to the rational use of Amazonian natural resources.